2006
DOI: 10.1186/1476-4598-5-57
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: The MUC1 gene encodes a mucin glycoprotein(s) which is basally expressed in most epithelial cells. In breast adenocarcinoma and a variety of epithelial tumors its transcription is dramatically upregulated. Of particular relevance to breast cancer, steroid hormones also stimulate the expression of the MUC1 gene. The MUC1 gene directs expression of several protein isoforms, which participate in many crucial cell processes. Although the MUC1 gene plays a critical role in cell physiology and pathology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 66 publications
(78 reference statements)
4
33
1
Order By: Relevance
“…1). In agreement with other reports (29), MCF-7 cells express high MUC1. Interestingly, H2073 and H1793 cells, derived from female patients, also express high MUC1 protein.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…1). In agreement with other reports (29), MCF-7 cells express high MUC1. Interestingly, H2073 and H1793 cells, derived from female patients, also express high MUC1 protein.…”
Section: Resultssupporting
confidence: 93%
“…We did not detect E 2 regulation of MUC1 mRNA in any lung adenocarcinoma cells, HBECs, or MCF-7 cells and conclude that E 2 does not regulate MUC1 in these cells. The difference between our results and those reported earlier in MCF-7 cells (29) is that we used Q-PCR rather than a MUC1-promoter-reporter and non-quantitative PCR. While the samples size is small, we observed no significant difference in MUC1/A and MUC1/B splice variant expression between lung adenocarcinoma cell lines derived from female versus male patients.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…The expression of MUC1 protein was observed in the 282 cytoplasm and along the cell membrane as previously mentioned 283 in literature [25][26][27][28]. Gene expression studies showed that MUC1 284 expression was reduced following treatment with two drug 285 cocktails: the first cocktail (i.e.…”
mentioning
confidence: 64%
“…ACOX2 up-regulation in the tumor conferred the same protective effect on mortality as MUC1 (mucin 1, cell surface associated 1q21). Variants of MUC1 interact with estrogen [30], and higher expression is associated with late stage epithelial ovarian cancer [31, 32] and prostate cancer [33]. …”
Section: Discussionmentioning
confidence: 99%